Virus-specific cytotoxic T lymphocytes differentially express cell-surface leukocyte immunoglobulin-like receptor-1, an inhibitory receptor for class I major histocompatibility complex molecules. - Antrobus, R; Khan, N; Hislop, A; Montamat-Sicotte, D; Garner, L; Rickinson, AB; Moss, P; Willcox, B (2005)
Leukocyte immunoglobulin-like receptor-1 (LIR-1) is an inhibitory receptor that negatively regulates T cell effector functions after interaction with host class I major histocompatibility complex molecules and, additionally, binds to UL18, a human cytomegalovirus (HCMV)-encoded class I homologue. Here, we demonstrate that virus-specific cytotoxic T lymphocytes (CTLs) differentially express LIR-1, with high frequencies of expression on HCMV-specific CD8+ T cells and intermediate and low frequencies of expression on influenza virus-specific and Epstein-Barr virus (EBV)-specific CTLs, respectively. Expression of LIR-1 was dependent on CTL-antigen specificity and was associated with a differentiated effector memory phenotype, as demonstrated by decreased expression of CD28 and increased expression of CD57. During primary HCMV and EBV infections, expression of LIR-1 on virus-specific CTLs was low and increased slowly. These results indicate that expression of LIR-1 increases during differentiation of virus-specific CD8+ effector T cells. Furthermore, they suggest that a potential immunoregulatory function of UL18 may be to preferentially target highly differentiated HCMV-specific effector memory T cells during persistent infection.